2014
DOI: 10.1073/pnas.1413789111
|View full text |Cite
|
Sign up to set email alerts
|

Single gene insertion drives bioalcohol production by a thermophilic archaeon

Abstract: Bioethanol production is achieved by only two metabolic pathways and only at moderate temperatures. Herein a fundamentally different synthetic pathway for bioalcohol production at 70°C was constructed by insertion of the gene for bacterial alcohol dehydrogenase (AdhA) into the archaeon Pyrococcus furiosus. The engineered strain converted glucose to ethanol via acetate and acetaldehyde, catalyzed by the host-encoded aldehyde ferredoxin oxidoreductase (AOR) and heterologously expressed AdhA, in an energy-conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 38 publications
3
80
1
Order By: Relevance
“…(19). "AdhA" was also used to describe the Pyrococcus furiosus short-chain dehydrogenase (adh_short) (20,21) (Fig. 3) and the PQQdependent alcohol dehydrogenases from Frateuria aurantia (22) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19). "AdhA" was also used to describe the Pyrococcus furiosus short-chain dehydrogenase (adh_short) (20,21) (Fig. 3) and the PQQdependent alcohol dehydrogenases from Frateuria aurantia (22) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3) into the hyperthermophilic archaeon P. furiosus, which has a unique aldehyde ferredoxin oxidoreductase (AOR) enzyme that reduces acetate to acetaldehyde but no native alcohol dehydrogenase. Wild-type P. furiosus does not produce ethanol; however, as a result of the adhA insertion, the engineered strain was able to generate ethanol from acetaldehyde and produced Ͼ20 mM ethanol from 5 g/liter cellobiose (21), demonstrating that the iron-containing AdhA can be used for ethanol production. Here, we show that adhA is important for ethanol production in a native adhA host.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of C. bescii to express this AOR demonstrates that it has a very active tungsten utilization pathway, an important factor to consider for future engineering strategies in this organism. For example, the recently discovered alcohol production pathway from organic acids, involving AOR and an aldehyde dehydrogenase, AdhA (35), might be applicable in this organism and other Caldicellulosiruptor species.…”
Section: Discussionmentioning
confidence: 99%
“…With a recombinant strain of Pyrococcus furiosus it was recently directly demonstrated that the acetaldehyde:ferredoxin oxidoreductase is involved in ethanol formation from acetic acid (82).…”
Section: H 2 Activationmentioning
confidence: 99%